Posted by Mike on Wednesday, January 30, 2013 at 7:12pm.
5x-6 = 2x+12
Combine like terms. Subtract 2x from both sides of the equation.
5x - 2x - 6 = 12
3x - 6 = 12
Add 6 to both sides.
3x = 12 + 6
3x = 18
Divide both sides by 3.
x = 18/3
x = 6
It looks like x does not equal 3. Let's try substituting 3 for x.
5x-6 = 2x+12
(5 * 3) - 6 = (2 * 3) + 12
15 - 6 = 6 + 12
Nope! 3 doesn't work.
You subtract 12 on both sides of the equal sign
Then you get 5x-18=2x
Subtract 5x on both sides
Divide by -3 both sides
You get x=6
Thank You That Is What I Got Also, But The Workbook Said x equaled 3
Im sorry but the books wrong
Math Help - This is a substitution equation. Would that change the steps that ...
Math33333 - Please help me! Problem: x+2 x-3 _________ - _________ 2x^2+5x+2 2x^...
math - 3x^2+6x/2x^2-11x+12 - 2x^2-5x+3/x^2+x-2 ÷ 4x^2-12x+9/x^2-4 I got ...
Hard algebra qestion - 3x^2+6x/2x^2-11x+12 - 2x^2-5x+3/x^2+x-2 ÷ 4x^2-12x...
Algebra - Can someone check my algebra answers and help me with the problems I ...
Algebra - Patchwork. A quilt patch cut in the shape of a triangle has a base of ...
math - it says to decide wether the graphs are parallel lines to explain my ...
Algebra - The answer in the book however says -(5x^2-17x-9)/(x-3)(x+2) so I don...
Math - Can someone please check my answers below for accurateness? The ...
College Algebra - I'm still having trouble with this problem. Can someone ...
For Further Reading